2008
DOI: 10.1002/hec.1354
|View full text |Cite
|
Sign up to set email alerts
|

Income, relative income, and self‐reported health in Britain 1979–2000

Abstract: We test the relative income hypothesis that an individual's health depends on the distribution of income in a reference group, as well as on the income of the individual. We use data on 231 208 individuals in Great Britain from 19 rounds of the General Household Survey between 1979 and 2000. Results are insensitive to the measure of self-assessed health used but the sign and significance of the effect of relative income depend on the reference group (national or regional) and the measure of relative income (Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 42 publications
8
82
0
1
Order By: Relevance
“…Recent evidence has shown that relative income has no eect on self-reported health (Jones and Wildman, 2007;Sutton, 2003, 2006;Lindley and Lorgelly, 2003;Miller and Paxson, 2006). Some of the arguments in favour of no relative income eect are that relative income may have a delayed eect only after 15 years (Subramanian and Kawachi, 2004) or due to omitted variable bias caused by not including area or year eects (Gravelle and Sutton, 2006). & This is a simplication recently applied in OECD studies to adjust household income for needs.…”
Section: Marginal Eectsmentioning
confidence: 99%
“…Recent evidence has shown that relative income has no eect on self-reported health (Jones and Wildman, 2007;Sutton, 2003, 2006;Lindley and Lorgelly, 2003;Miller and Paxson, 2006). Some of the arguments in favour of no relative income eect are that relative income may have a delayed eect only after 15 years (Subramanian and Kawachi, 2004) or due to omitted variable bias caused by not including area or year eects (Gravelle and Sutton, 2006). & This is a simplication recently applied in OECD studies to adjust household income for needs.…”
Section: Marginal Eectsmentioning
confidence: 99%
“…Finally, if 3 > 0 the comparison income has a greater e¤ect on the poor. 17 Gravelle and Sutton (2009) introduce the same measure for studying the relationship between perceived health and income in the UK. We …nd its design appropriate to our purpose as well, because we want to test for asymmetries in the impact that relative income might have on the relatively poor and the relatively rich in the comparison group.…”
Section: Income Relative Income and Deprivationmentioning
confidence: 99%
“…Judge et al, 1998;Deaton, 2001;Gravelle et al, 2001;Deaton and Lubotsky, 2003;Gerdtham and Johannesson, 2004;Gravelle and Sutton, 2008). Most of the literature has used crosssectional data sets that do not allow controlling for unobservable heterogeneity that is associated with regions/countries and years.…”
Section: Introductionmentioning
confidence: 99%